PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI PERMASALAHAN SISWA SELAMA MASA PANDEMI COVID-19 DI MI MUHAMMADIYAH KARANGANYAR - Rifayani, Hastuti (JURNAL TALENTA PSIKOLOGI, 2022)
The COVID-19 pandemic has had a major impact on changes in the education system. Various problems arise as a result of these changes. This requires proper handling. The role of BK teachers is very important for the success of the education system. This study aims to understand in depth the role of guidance and counseling teachers in overcoming student problems during the Covid-19 pandemic at MI Muhammadiyah Karanganyar. This research is a type of descriptive qualitative research. Data collection techniques used are interviews, observation and documentation. The informants of this research were selected by purposive sampling technique. The main informants are BK teachers while the supporting informants are subject teachers and students. The results showed that the problems faced by students during the pandemic were disciplinary problems and problems with parental study assistance at home. Meanwhile, the services provided by BK teachers are information service programs and counseling programs. Information service programs are in the form of educational programs for parents and motivational programs for students. While the counseling program is in the form of on-line counseling and home visits.